2002
DOI: 10.1021/la025660r
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gelling Behavior of Poly(N-isopropylacrylamide-co-vinyl laurate) Microgel Dispersions

Abstract: Aqueous colloidal microgel particles prepared from N-isopropylacrylamide (NIPAM) co-polymerized with different ratios of the comonomer vinyl laurate have been investigated with respect to their physicochemical properties and colloid stability. The hydrodynamic diameters of microgel particles synthesized using 10% and 50% w/v vinyl laurate have been examined. The poly(NIPAM)-co-vinyl laurate microgel particles, suspended in water, show similar conformational behavior to poly(NIPAM) microgels in that they revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
1
33
1
Order By: Relevance
“…It is noted that the temperature-dependent interparticle potential is also responsible to the formation of reversible or irreversible aggregates in colloidal systems of PNIPAM derivatives. [30] The physical bonding may also be caused by the hydrophobic interaction between the neighboring PNIPAM networks. More convin- cing evidences are needed to determine the exact origin of the attractive force that bonds the IPN nanoparticles into a network at T > T g .…”
Section: ±1mentioning
confidence: 99%
“…It is noted that the temperature-dependent interparticle potential is also responsible to the formation of reversible or irreversible aggregates in colloidal systems of PNIPAM derivatives. [30] The physical bonding may also be caused by the hydrophobic interaction between the neighboring PNIPAM networks. More convin- cing evidences are needed to determine the exact origin of the attractive force that bonds the IPN nanoparticles into a network at T > T g .…”
Section: ±1mentioning
confidence: 99%
“…In this case, the highly swollen microgel particles are physically closepacked to form a macroscopic gel. [17] Benee et al [18] reported that when heated to 40 8C in a NaCl solution, the copolymer microgel of NIPAM and vinyl laurate form irreversible flocs and macroscopic gels above a critical electrolyte concentration. Due to the usage of a special comonomer, the gelling behavior may be attributed to the association among the laurate groups.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 6 is the plot of the hydrodynamic diameter of pNIPAM-nG-2% (n = 1, 3,9,14) microgels changing with temperature. The deswelling behavior of pNIPAM-nG-2% microgels monitored by DLS was in good agreement with other methods.…”
Section: Volume-phase Transition Behaviormentioning
confidence: 99%
“…Wu and Zhou [11] proposed that this is due to the inhomogeneity of the subchain length between two neighboring crosslinking points inside the gel. In fact, a number of other factors, such as structure and concentration of the crosslinking agent used [12,13], incorporation of co-monomers [14,15], properties of solvents [16,17], and surfactants [18] also have a strong influence on phase behavior of microgels. K. Kratz et al [12] have investigated the volume-phase transition of pNIPAM microgels crosslinked by triethyleneglycol dimethacrylate (TREGDMA), ethyleneglycol dimethacrylate (EGDMA), and N, N -methylenebis(acrylamide) (BIS) and found that EGDMA-and TREGDMA-crosslinked microgels showed similar swelling behavior, whereas the swelling capacity of the BIS-crosslinked microgels was much lower.…”
Section: Introductionmentioning
confidence: 99%